Nwanyibuife - Ausbeth-Ajagu, Anuli (Literamed Publications Nigeria Ltd, 2003)
An interesting play that is strikingly gender sensitive just as the title Nwanyibuife implies( a woman is something). The work attempts to give the woman and indeed the world in general an insight into the male dominated world of the women within and outside marriage.
Keywords: Drama